Influence of coping strategies in the specific worries of pregnancy - Carmona-Monge, Francisco J; Marín-Morales, Dolores; Peñacoba-Puente, Cecilia; Carretero-Abellán, Isabel; Moreno-Moure, María A. (Anales de Psicología / Annals of Psychology, 2012)
The aim of this study is to analyse the influence of the different coping strategies on specific pregnancy-related worries. We assessed a sample comprised of 285 pregnant women during the first half of pregnancy who underwent the Coping Strategies Questionnaire, and the Cambridge Worry Scale. In addition, sociodemographic variables were collected (age, education, prior pregnancies, occupational situation and pregnancy planning). We observed a significant relationship between pregnancy-related worries and negative auto-focused coping, overt emotional expression coping and avoidance coping. Regression analysis revealed a significant influence of negative auto-focused coping and number of children on pregnancy-related worries. These results suggest that coping characterised by perception of incapacity to handle situations has a negative effect on the pregnant woman’s psychological condition. The experience of a prior birth could reduce this effect. Therefore, we highlight the importance of psychological care for the pregnant woman with the purpose of, from the onset of gestation and especially in women pregnant for the first time, developing resources to adapt to the new situation and improve women’s health